Sosialisasi Pemupukan Berimbang Dan Kunjungan Distributor Di Desa Jawa Timur - Raihan Bimo Lazuardi; Ika Sari Tondang; Nuriah Yuliati (Lembaga Pengembangan Kinerja Dosen, 2024)
Tillage is an activity that aims to increase soil fertility, improve soil structure and create good soil conditions for plant growth. Soil processing can be done in several ways, one of which is the application of fertilizer to plants. Farmers' understanding of efficient and effective fertilization methods is still not fully mastered. Most farmers often fertilize plants beyond the recommended dose. This community service activity aims to (1) farmers can understand knowledge about non-subsidized fertilizer products from PT. Petrokimia Gresik, (2) increase farmers' understanding and knowledge of fertilizer quality and balanced fertilization technology to achieve relatively efficient fertilizer use, (3) farmers can understand the condition of private land and understanding of the amount and type of fertilizer PT Petrokimia Gresik needed. The methods used include surveys, socialization, and practical demonstrations regarding soil testing of farmers in Putat Lor Village, Tajinan District, Malang. Based on this socialization activity, the results obtained are (1) the knowledge of farmers in Putat Lor Village regarding non-subsidized fertilizer products from PT Petrokimia Gresik is increasing (2) increasing knowledge of farmers in Putat Lor Village about fertilizer quality and balanced fertilization technology (3) farmers in Putat Lor Village know the condition of the soil from private land through soil test practices so that they can estimate the type and amount of fertilizer to be used.